2018
DOI: 10.3390/min8040154
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Total Organic Carbon Estimation of the Eagle Ford Shale with Density Logs by Considering the Effect of Pyrite

Abstract: Pyrite is a common mineral with a higher density than most other minerals in the Eagle Ford Shale formation. Hence, if pyrite is not considered in the total organic carbon (TOC) estimation, based on density logs, it may lead to errors. In order to improve the accuracy of the TOC estimation, we propose an updated TOC estimation method that incorporates the concentration of pyrite and organic porosity. More than 15 m of Eagle Ford Shale samples were analyzed using Rock-Eval pyrolysis, X-ray fluorescence (XRF), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 20 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…The linear relation between TOC and bulk density was established, and subsequently, it was found that shale rock density falls as the TOC value drops. 50 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The linear relation between TOC and bulk density was established, and subsequently, it was found that shale rock density falls as the TOC value drops. 50 …”
Section: Resultsmentioning
confidence: 99%
“…The linear relation between TOC and bulk density was established, and subsequently, it was found that shale rock density falls as the TOC value drops. 50 Theoretically, the shale's organic matter density (1.02−1.11 g/cm 3 ) is less than that of the other part of the rock matrix. Therefore, because of the presence of organic matter in low porosity and permeability shale, rock formation density decreases as the organic content increases.…”
Section: Porosity and Saturationmentioning
confidence: 99%
“…We have compiled a study of multiple shale formations focusing on those in the United States. The estimation of the mechanical properties of the formation is primarily taken from Dobson and Houseworth (2013) and other authors (Schwartz et al 2019;Kong et al 2023;Zhou et al 2023;Jin et al 2018;Jiang et al 2018). We assume a slickwater injection into horizontal wells.…”
Section: Representative Casesmentioning
confidence: 99%